2014
DOI: 10.22436/jmcs.013.02.01
|View full text |Cite
|
Sign up to set email alerts
|

Fuzzy Semi Open Soft Sets Related Properties In Fuzzy Soft Topological Spaces

Abstract: In the present paper, we continue the study on fuzzy soft topological spaces and investigate the properties of fuzzy semi open (closed) soft sets, fuzzy semi soft interior (closure), fuzzy semi continuous (open) soft functions and fuzzy semi separation axioms which are important for further research on fuzzy soft topology. In particular, we study the relationship between fuzzy semi soft interior fuzzy semi soft closure. Moreover, we study the properties of fuzzy soft semi regular spaces and fuzzy soft semi nor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…They showed that soft sets are class of special information system. In the recent year, many interesting applications of soft sets theory have been extended by embedding the ideas of fuzzy sets [12][13][14][15][16][17][18][19][21][22][23] industrialized soft set theory , the operations of the sets are redefined and in indecision making method was constructed by using their new operations [24]. Recently, in 2011, Shabir and Naz [24] launched the study of soft Topological spaces, they beautiful defined soft Topology as a collection of τ of soft sets over X.…”
Section: Introductionmentioning
confidence: 99%
“…They showed that soft sets are class of special information system. In the recent year, many interesting applications of soft sets theory have been extended by embedding the ideas of fuzzy sets [12][13][14][15][16][17][18][19][21][22][23] industrialized soft set theory , the operations of the sets are redefined and in indecision making method was constructed by using their new operations [24]. Recently, in 2011, Shabir and Naz [24] launched the study of soft Topological spaces, they beautiful defined soft Topology as a collection of τ of soft sets over X.…”
Section: Introductionmentioning
confidence: 99%
“…B.Ahmad and A.Kharral [3] investigated fuzzy soft sets and established Fuzzy soft functions on Fuzzy soft classes. The notion of topological structure of Fuzzy soft sets was introduced by Tanay and Kandemir [4] in 2011 and studied further by Varol and Aygun [5].…”
Section: Introductionmentioning
confidence: 99%
“…They showed that soft sets are class of special information system. In the recent year, many interesting applications of soft sets theory have been extended by embedding the ideas of fuzzy sets industrialized soft set theory, the operations of the soft sets are redefined and in indecision making method was constructed by using their new operations [9][10][11][12][13][14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%